2022
DOI: 10.1103/physrevlett.129.132501
|View full text |Cite
|
Sign up to set email alerts
|

Charge Radii of Ni55,56 Reveal a Surprisingly Similar Behavior at N=28

Abstract: Nuclear charge radii of 55;56 Ni were measured by collinear laser spectroscopy. The obtained information completes the behavior of the charge radii at the shell closure of the doubly magic nucleus 56 Ni. The trend of charge radii across the shell closures in calcium and nickel is surprisingly similar despite the fact that the 56 Ni core is supposed to be much softer than the 48 Ca core. The very low magnetic moment μð 55 NiÞ ¼ −1.108ð20Þ μ N indicates the impact of M1 excitations between spin-orbit partners ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 72 publications
3
8
0
Order By: Relevance
“…Within uncertainties all ratios agree well with the average of A u /A l = 0.3894 (6), showing no sign of higher order nuclear contributions to the A constants beyond the point-like nuclear magnetic dipole moment, enabling the use of Eq. ( 1).…”
Section: Normalized Photon Countssupporting
confidence: 61%
See 1 more Smart Citation
“…Within uncertainties all ratios agree well with the average of A u /A l = 0.3894 (6), showing no sign of higher order nuclear contributions to the A constants beyond the point-like nuclear magnetic dipole moment, enabling the use of Eq. ( 1).…”
Section: Normalized Photon Countssupporting
confidence: 61%
“…The doubly magic 56 Ni plays a major role in stellar nucleosynthesis [2][3][4][5]. Recently, the nuclear charge radii of the neutron-deficient isotopes 54−56 Ni [6] and the neutronrich isotopes [58][59][60][61][62][63][64][65][66][67][68]70 Ni [7] were determined using collinear laser spectroscopy at NSCL/MSU and ISOLDE/CERN, respectively. Density functional, coupled-cluster and valence-space in-medium similarity renormalization group (VS-IMSRG) calculations were performed and used to benchmark different Hamiltonians and many-body methods.…”
Section: Introductionmentioning
confidence: 99%
“…For the traditional magic numbers of 28 and 50, Ref. [18] provided the first direct experimental evidence for the doubly magic nature of , and this experiment also confirmed the existence of a deformed second low-energy state, supporting the prediction of shape coexistence in [19]. The first measurement of the charge radius of provides direct support for its doubly magic nature [20].…”
Section: Introductionsupporting
confidence: 60%
“…In addition, we found that the DRHBc calculations support the appearance of the subshell closures at at the mean-field level for most of the isotopic chains in question but the available data do not. This is related to the island of inversion of [17,19,76,77]. A proper theoretical description of this mass region needs to consider beyond-mean-field effects.…”
Section: B Two-neutron Separation Energies S 2nmentioning
confidence: 99%
“…This puzzle was solved by the introduction of chiral EFT three-body forces [10]. These contributions have been studied extensively in subsequent works, especially in comparison with mass [11][12][13][14][15][16], charge radius [17][18][19][20][21][22][23], and electromagnetic moment [24][25][26] measurements of neutron-rich systems. The present challenge is to obtain unambiguous experimental measurement to compare to different ab-initio calculations to improve their accuracy and predictive power.…”
mentioning
confidence: 99%